Medkulturnost v romanu Maje Haderlap Engel des Vergessens / Angel pozabe in strategija prevoda v slovenščino - Borovnik, Silvija (Przekłady Literatur Słowiańskich, 2016)
Międzykulturowość w powieści Mai Haderlap Engel des vergessens / Angel pozabe i strategie tłumaczenia na język słoweński (tłum. Joanna Cieślar) Interculturality in Maja Haderlap’s novel Angel of Oblivion and strategies of translation into Slovene In 2011, the publication house Wallstein published the novel by the Carinthian Slovene Author, Maja Haderlap, which attracted a lot of attention. Firstly, the novel is special because it tells a somewhat unknown and oftentimes concealed tale about the agony of the Carinthian Slovenes during the Second World War. This narrative is being revived by the author on the basis of her grandmother’s narration and other relatives, who were deported to Nazi concentration camps during the war because they were suspected of collaboration with the partisans. Secondly, this novel is special because of its emphasis on a woman’s war story which is usually marginalized in historical accounts. The third peculiarity of this novel is demonstrated by the fact that the novel was written by a female Slovene author in the German language. The author substantiated her writing on the rationale that the German language offered her the emotional distance and that she wanted to draw from the subject, which was not well‑recognized in the German‑speaking environment, being nearer to Austrian rather than German readers. On the basis of the autobiographical elements, she has spoken about the discrimination of the Slovenes and also about the disdain and disavowal of the Slovene language. Nevertheless, the writer, Florjan Lipuš, has labeled her novel as linguistic and national heresy in his work Enquiry for the Name (Poizvedovanje za imenom, 2013). He thought that the Slovene language on the artistic level should be taken care of by those that are gifted and creative and that writing literature in the Slovene language means its preservation. His critique of Maja Haderlap’s linguistic crossing into German is also very harsh because this is not the only such case of writers of the younger or middle‑aged generation of Carinthian Slovenians writing in German. Maja Haderlap’s novel was translated into Slovene by Štefan Vevar, who is himself of Carinthian origin. This is especially important because the translator has demonstrated not only the role of the Slovene language in this novel but also has included in his innovative translation some elements of the Carinthian dialect, which is the mother tongue of the author and her literary characters. With these translation solutions, Vevar preserved the original’s linguistic duality and also demonstrated that this novel, which was written in German, is also Slovene. However, the author of this novel belongs to the group of writers with a double, interculturally designated identity. Key words: Maja Haderlap’s novel The Angel of Oblivion, Slovene translation, bilingualism, interculturality